What hedge funds really do : an introduction to portfolio management - Romero, Philip J. (2014 digital library., 2014)
What do hedge funds really do? These lightly regulated funds continually innovate new investing and trading strategies to take advantage of temporary mispricing of assets (when their market price deviates from their intrinsic value). These techniques are shrouded in mystery, which permits hedge fund managers to charge exceptionally high fees. While the details of each fund's approach are carefully guarded trade secrets, this book draws the curtain back on the core building blocks of many hedge fund strategies.